A Giant Foreign Body Granuloma in a Captive Chinese Monal (Lophophorus lhuysii) Caused by Gizzard Perforation - Feng, Shaohua (2024)
Background: Chinese Monal (Lophophorus lhuysii) is an endangered bird that lives in high altitude areas of southwestern China. The only captive population of Chinese Monal in the world is in a reserve in Sichuan. Despite the great efforts made by the reserve and researchers, the population of captive Chinese Monal has increased slowly. Disease is one of the main factors causing the death of captive Chinese Monal, but there are few reports on their diseases. This study reports a rare case of gizzard perforation in birds and is the 1st reported death case of Chinese Monal, which can provide a reference for related clinical symptoms and pathological diagnosis of wild birds. Case: The female Chinese Monal was rescued from a natural reserve and raised in the administrative center for a long time because it was unable to walk normally. On December 4 of the 3rd year, the Chinese Monal presented with severe loss of appetite, depressed spirit, unable to stand, and eventually died. We performed a necropsy on the Chinese Monal and observed and recorded the pathological changes. The tissues were collected to make pathological sections and stain for histopathological diagnosis. Necropsy observation revealed that the keel bone was abnormally protruded, the abdomen was significantly enlarged, a giant foreign body granuloma in the abdominal cavity was found closely adhered with the gizzard through a hole, and all intestinal segments were thin and stenosed. Histopathological observation revealed that the structure under the stratum corneum of the gizzard and the mucosa of all intestinal segments were not integrated, necrosis was found in the liver, vacuolar degeneration was found in pancreatic acinar cells, and the lymphocytes were significantly decreased in the cecal tonsil and spleen. These results suggest that the digestive system and immune system were damaged by the compression of foreign body granuloma. Discussion: Compared to other causes of gastric perforation, accidental ingestion of sharp foreign bodies is relatively rare. Consistent with the existing reports of birds, foreign body granuloma is accompanied by gizzard perforation and is filled with contents. The foreign body granuloma was extremely large in this case, with a length of 16 cm and a weight of 500 g, reaching 1/5 of the body weight, occupying almost the entire abdominal cavity, causing severe compression on the abdominal organs. However, no foreign body was found in the necropsy, and it may have been crushed by gravel in the gizzard and excreted. We speculate that the cause of death based on the lesions found in necropsy and pathological diagnosis was as follows: a sharp foreign matter was ingested by Chinese Monal accidentally, causing perforation of the gizzard, and the leaked food stimulated the body to form a foreign body granuloma in the abdominal cavity. The volume of the foreign body granuloma gradually increased and compressed the abdominal artery, causing chronic mesenteric ischemia. The ingestion and digestion functions were impaired, inducing severely malnourished and extremely emaciated, finally leading to multiple organ failure and death. As a result, the captive environment is very important for animal health. In daily feeding management, more attention should be paid to the safety of the captive environment. Keywords: Chinese Monal, bird, captive, gastric perforation, foreign body, granuloma, clinical necropsy, pathological diagnosis.